PENGGUNAAN PLATFORM REVERSO DALAM PERKULIAHAN BAHASA ARAB PADA MAHASISWA PAI UNU PURWOKERTO - Yurianto, Ramdhan; Farhani Mubarokah; Maulidia Apriliana, Lulu (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
The Reverso platform is not a new platform, however, there are still many who do not know about the Reverso platform as an Arabic learning platform . This study aims to describe, what is the reverso platform, how is the picture of Arabic learning by utilizing the reverso platform, student perceptions and lecturer responses to the reverso platform, advantages and disadvantages of using the reverso platform in lectures. This research uses qualitative methods with a descriptive approach. The source of this research data is through a questionnaire that researchers shared using a google form that was distributed online to students using the whatsapp application with 10 questions to students, namely to find out students' opinions about the reverso platform in Arabic lectures, secondly to explore lecturers' views on the features of the reverso platform. Data collection techniques using observation, interviews, and documentation. The results of this study show that the implementation of the reverso platform is easy and suitable for Arabic lectures and increases student motivation to be active in lectures and assignments and is recommended for other courses.